União internacional dos magistrados: diplomacia e “soft power” nas relações internacionais - Dornelles Junior, Paulo Roberto (2024)
The International Association of Judges – IAJ is a private international body founded in Austria in 1953 and headquartered in Rome. The entity defends the independence of the judiciary, as a guarantee of human rights and freedom, and among other objectives works in judicial education, having four study commissions. It is made up of associations of judges from around ninety countries, which are structured into regional groups. It has consultative status at the United Nations Economic and Social Council - ECOSOC, the International Labor Organization – ILO and the Council of Europe. Collaborates with the United Nations Special Rapporteur for the Independence of Judges and Lawyers. It holds international congresses, seminars and meetings. It works with national governments and international organizations on topics within its competence. Despite its potential international relevance, the entity is not the object of specific study in the field of international relations. This dissertation aims to fill this theoretical gap with a descriptive and critical-analytical examination of the entity and its performance in the world of international relations. This study is based on bibliographical and documentary research and situated knowledge, given the author's participation in the organization. The first part of the study examines the history and functioning of the IAJ, with references to Brazilian participation. Specific cases of action are explored: Prison of Turkish Judges; Independence of Polish Judges; Report on the Judiciary during the Pandemic; Afghan Women Judges and the Return of the Taliban, as well as reactions from the USSR and the People's Republic of China. The second part of the study proposes the theoretical framework of the entity in the academic universe of international relations. It begins with an analysis of texts about the entity and is contextualized with the intersection between law and international relations. The theoretical framework of the entity's operations is subsequently examined from the following perspectives: (a) influence and “soft power”; (b) transnational judicial dialogue and judicial diplomacy; and (c) conceptual dialogues between judicial diplomacy and paradiplomacy. Our conclusions follows.